PEMBERANTASAN PENYAKIT MALARIA DI INDONESIA OLEH WORLD HEALTH ORGANIZATION (WHO) MELALUI GLOBAL MALARIA PROGRAMME - Su'ud Banun Usnawas (Global Political Studies Journal, 2017)
The results of this study indicate that the process of implementing the malaria program in Indonesia was carried out in several stages through ACT treatment, spraying the walls of the house and distributing bed nets. Regarding its development, WHO has succeeded in increasing the percentage of low endemic areas with the distribution of bed nets and also through early age prevention where treatment is given to pregnant women and newborns. But in its implementation, WHO faces several obstacles and challenges such as lack of public awareness in rural areas that tend to be difficult to change, drastic climate change, access and infrastructure in Papua, West Papua and NTT areas and several other factors. The elimination of malaria in Indonesia can be said to be successful where it can be seen from the percentage in high endemic areas where declines have occurred and activities carried out through the central ministry have yielded results in which Indonesia stated that the percentage of endemic areas increased with 74% in malaria-free areas.